1980
DOI: 10.1002/pssa.2210590150
|View full text |Cite
|
Sign up to set email alerts
|

Role of quantum mechanisms and thermal heating in low-temperature creep of metals

Abstract: The temperature dependence of the creep rate jump in single crystals of cadmium and zink during temperature increment is studied in the range of 1.5 to 80 K. Also studied is the creep jump behaviour δϵNS during the N–S transition in pure lead, in alloys with abnormal heat conductivity, as well as lead alloys with paramagnetic admixture of nickel. It is shown that the observed peculiarities of the low temperature creep of metals are at sharp variance with the local thermal heating hypothesis. Experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Early proponents included [20,24,26,27]. Conversely, subsequent work by [13,22,23] suggests that, even to 4 K, creep is time-dependent and is a result of the thermal activation of dislocations.…”
Section: Discussion Of the Mechanisms Of Low-temperature Creep Logarimentioning
confidence: 91%
See 2 more Smart Citations
“…Early proponents included [20,24,26,27]. Conversely, subsequent work by [13,22,23] suggests that, even to 4 K, creep is time-dependent and is a result of the thermal activation of dislocations.…”
Section: Discussion Of the Mechanisms Of Low-temperature Creep Logarimentioning
confidence: 91%
“…Seeger et al [19,33,34] proposed a dislocation intersection mechanism for pure FCC metals under polyslip. Others have suggested that creep occurs due to quantum mechanical tunneling of dislocations at very low temperature [13,20,22,24,26,27], but there is no consensus as to the actual mechanisms involved.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Exceptional reviews of the widespread studies on the topic may be found in some important references [80][81][82]. Also, some studies were done regarding the proposition of quantum mechanical tunneling of dislocations at very low temperature [83][84][85][86][87][88].…”
Section: Creep 200mentioning
confidence: 99%